2021
DOI: 10.1007/s11224-020-01723-5
|View full text |Cite
|
Sign up to set email alerts
|

Combination and tricombination therapy to destabilize the structural integrity of COVID-19 by some bioactive compounds with antiviral drugs: insights from molecular docking study

Abstract: Recently, the SARS-CoV-2 (COVID-19) pandemic virus has been spreading throughout the world. Until now, no certified drugs have been discovered to efficiently inhibit the virus. The scientists are struggling to find new safe bioactive inhibitors of this deadly virus. In this study, we aim to find antagonists that may inhibit the activity of the three major viral targets: SARS-CoV-2 3chymotrypsin-like protease (6LU7), SARS-CoV-2 spike protein (6VYB), and a host target human angiotensin-converting enzyme 2 (ACE2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 40 publications
(73 reference statements)
0
11
0
Order By: Relevance
“…Due to highly frequent recurrent genetic recombination SARS- CoV-2 as emerged notably in the spike glycoprotein's RBD [ 29 ]. Marine-derived compounds such as oleic acid, saringosterol, -Sitosterol, Caulerpin, Glycoglycerolipids, Kjellmanianone, and Loliolide extracted from red, green, and brown macroalgae were recently reported as candidate inhibitors against 3CL pro , the Spike protein, and the ACE-2 receptor of SARS-CoV-2 in a molecular docking-based study [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Due to highly frequent recurrent genetic recombination SARS- CoV-2 as emerged notably in the spike glycoprotein's RBD [ 29 ]. Marine-derived compounds such as oleic acid, saringosterol, -Sitosterol, Caulerpin, Glycoglycerolipids, Kjellmanianone, and Loliolide extracted from red, green, and brown macroalgae were recently reported as candidate inhibitors against 3CL pro , the Spike protein, and the ACE-2 receptor of SARS-CoV-2 in a molecular docking-based study [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…and phlorotannins isolated from marine algae Eckolina cava were able to target SARS 3CL pro through in vitro studies (De Lira et al, 2007;Park et al, 2013). A molecular docking-based study recently reported the antiviral potential of marine-derived compounds including oleic acid, saringosterol, β-Sitosterol, Caulerpin, Glycoglycerolipids, Kjellmanianone, and Loliolide isolated from red, green, and brown macroalgae as candidate inhibitors against 3CL pro , the Spike protein, and the ACE-2 receptor of SARS-CoV-2 (El-Mageed et al, 2021). Another study also reviewed the therapeutic role of Spirulina algae-derived nutraceuticals in boosting the adaptive and innate immunity against coronavirus as well as other viral diseases (Ratha et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis was tested by Abdelrheem's group, who evaluated the inhibition of 6LU7 using several active natural products including caulerpin [4] . Their study showed that caulerpin may be used as a potential candidate for COVID‐19 treatment, and there sare already plans of further exploring the use of Caulerpin in coronavirus triple therapy [4c] …”
Section: Introductionmentioning
confidence: 99%